Buffalo nationalism : a critique of spiritual fascism - Ilaiah, K. (Kancha), 1952- (SAGE Publications Pvt Ltd, 2019)
The book argues forcefully for social justice for the vast majority of Indians, the Dalit-Bahujans, who remain socially, economically and culturally deprived.